Análise proeônica de tecido foliar de genótipo de cana-de-açúcar (Saccharum spp.) submetidos ao estresse hídrico - Viana, Luciana da Silva (2010)
Hydric deficit is one of the main limiting factors for the sugarcane productivity increase in the Brazilian northeast. The process can be worsened due to the global climatic changes and it is estimated the episodes of hydric restrictions will be much more frequent, including in other cultivation areas in Brazil. When plants are submitted to the hydric stress, there is an induction of a series of genes and specific proteins as an adaptation mechanism to this condition. Therefore, proteome studies can be a powerful tool to identify proteins and find out their mechanisms of response and adaptation to the hydric stress. The present study aimed to evaluate changes in the proteome of the RB72910 (tolerant of the hydric stress) and RB72454 (sensitive) genotypes of sugarcane as well to identify the proteins involved when submitted to hydric stress. To carry out these goals, plants were cultivated in a greenhouse, and after two months of cultivation (control), the irrigation was suspended for 2 days (stress), which was monitored by the hydric potential determination (Ψw). After this period, the irrigation was restarted for two more days (recovery). For the proteome analysis, three extraction methods to prepare protein samples for two-dimensional electrophoresis were tested. The method that presented the best results on the number of spots, quality and reproducibility of the gels was the adapted method of phenol extraction. Results showed the presence of several exclusive spots with differences in the expression between sensitive and tolerant genotypes. It was detected 480 spots for the sensitive genotype and 352 spots for the tolerant genotype, and a total of 80 spots were identified by mass spectrometry (MS-MALDITOF) after the proteome analysis for the control, stress and recovery treatments. It was possible to see between both genotypes that 24% of the proteins identified and related to the stress were present in the tolerant genotype, while just 3% of the proteins associated to the hydric stress were observed in the sensitive genotype. The MS analysis of the identified spots showed the presence of proteins such as chaperona, ascorbato peroxidase, superoxide dismutase, heat shock, 14,3-3-like and isoflavone reductase, which have been described to participate in the plant defense mechanisms against biotic and abiotic stresses.